The role of immunotherapy in early-stage and metastatic NSCLC - Attila Lieber; Attila Makai; Zsuzsanna Orosz; Tamás Kardos; Susil Joe Isaac; Ilona Tornyi; Nóra Bittner (Frontiers Media S.A., 2024)
In the past decade we have seen new advances and thus remarkable progress in the therapeutic options for non-small cell lung cancer (NSCLC). Among cytostatic therapies with new approaches in molecularly targeted therapies, we see new developments in a wide range of applications for immunotherapies. In this review we discuss the new potential modalities for the use of immune checkpoint inhibitors (ICIs) in the frontlines, including in early-stage (perioperative) and metastatic settings. The perioperative use of ICIs in both neoadjuvant and adjuvant settings may show benefits for patients. In early-stage NSCLC (from stage IIB and above) a multimodality approach is recommended as the gold standard for the treatment. After surgical resection platinum-based adjuvant chemotherapy has been the standard of care for many years. Based on the benefit of disease-free survival, the approval of adjuvant atezolizumab and adjuvant pembrolizumab was a significant breakthrough. In the metastatic setting, the use of immune checkpoint inhibitors with chemotherapy, regardless of PD-L1 expression or ICI alone (PD-L1 expression equal to or greater than 50%) also improves overall survival and progression-free survival.